Construction of an Individual Educational Trajectory as a Way to Reveal the Personal and Proffesional Potential of a Future Teacher - Klieba, Anna; Bludova, Yuliia; Galushko, Nataliia; Pavlova, Olena; Pylypenko, Nataliia (My University, 2020)
The construction of an individual educational trajectory changes due to a change in approaches to the personal and professional potential of the future teacher. Provided that the acquisition of professional skills by a teacher has not required constant training throughout life, then the modern environment requires a systematic updating of skills and advanced training. In fact, approaches to training and the role of the teacher in the educational environment are changing. Based on an integrative literature review, the trends of individual educational tools for the development of the personal and professional potential of a future teacher within EU have been investigated. The academic paper has revealed significant differences regarding the disclosure of personal and professional potential of future teachers within EU. Differences include: teachers’ training, the establishment of additional requirements for teachers in addition to curricula, regulating teachers’ mobility, professional and personal support, continuing professional development. The article has stated that induction and mentoring for new teachers is widespread within EU and legally established in most European countries. The investigation attests to the fact that induction may play a key role in supporting teachers’ professional development. Induction programs combine elements of mentoring, training, peer review, and scheduled meetings with school principals and colleagues to provide personal, social, and professional support. Induction activity is connected with increased self-efficacy and job satisfaction. Mentoring programs are designed taking into consideration the school context. Pupils’ knowledge, classroom pedagogy, assessment of pupils and harmonization of curriculum standards differ significantly between primary and secondary schools. Supporting measures to promote teachers’ participation have been developed in almost all EU countries.
Construction of an Individual Educational Trajectory as a Way to Reveal the Personal and Proffesional Potential of a Future Teacher / A. Klieba, Y. Bludova, N. Galushko, O. Pavlova, N. Pylypenko // International Journal of Higher Education : Published by Sciedu Press / Canada, 2020. – Vol. 9. – No. 7. – P. 73–83.
Keywords: професійна компетентність, освітні програми ЄС (навчальні програми), наставництво, програми наставництва, особистий потенціал вчителів, професійний потенціал вчителів, розвиток учительського потенціалу, постійний професійний розвиток; professional competence, EU educational programs (curricula), mentoring, mentoring programs, personal potential of teachers, professional potential of teachers, development of teacher’s potential, continuing professional development (CPD); профессиональная компетенция, образовательные программы (учебные планы), наставничество, программы наставничества, личный потенциал учителей, профессиональный потенциал учителей, развитие потенциала учителей, непрерывное профессиональное развитие